2022
DOI: 10.3390/vaccines10010078
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cytokines in Metastatic Breast Cancer Patients Select Different Prognostic Groups and Patients Who Might Benefit from Treatment beyond Progression

Abstract: Cancer induces immune suppression to overcome its recognition and eradication by the immune system. Cytokines are messengers able to modulate immune response or suppression. There is great interest in the evaluation of their changes during treatment in order to identify their relationship with clinical outcome. We evaluated 18 cytokines in breast cancer patients treated with eribulin before starting treatment (T0) and after four courses of therapy (T1). Longitudinal modifications were considered and cytokine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
8
0
4
Order By: Relevance
“…Elevated serum levels of IL-10 have been found in breast cancer patients compared to healthy controls, and IL-10 serum levels correlated with cancer stage [ 30 , 31 ]. To our knowledge, serum IL-10 has not previously been shown to be an independent prognostic marker for survival in MBC, only in combination with other serum cytokines [ 31 , 32 ]. In our study, elevated serum levels of IL-10 were shown to be an independent prognostic factor for both worse OS and PFS in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum levels of IL-10 have been found in breast cancer patients compared to healthy controls, and IL-10 serum levels correlated with cancer stage [ 30 , 31 ]. To our knowledge, serum IL-10 has not previously been shown to be an independent prognostic marker for survival in MBC, only in combination with other serum cytokines [ 31 , 32 ]. In our study, elevated serum levels of IL-10 were shown to be an independent prognostic factor for both worse OS and PFS in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has used PCA to identify a cytokinome signature able to discriminate different prognostic groups among end-stage patients affected by different solid tumors [ 44 ] and in breast cancer patients to identify a signature potentially able to select patients for treatment beyond progression [ 45 ]. However, to the best of our knowledge, this is the first study on colorectal cancer using PCA to evaluate a cytokine profile in patients with metastatic disease treated with standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In BC, the Th2 pattern is associated with developing tumors with worse prognosis and survival. ( Paccagnella et al., 2022 ; Abeen, et al, 2018 ). Even though reduced IL-12 has been reported in BC patients ( Tzang et al., 2020 ), we did not observe this change when considering the BMI categorization.…”
Section: Discussionmentioning
confidence: 99%